2016
DOI: 10.1111/jfbc.12346
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds profile and antioxidant activity of commercial tropical red wines (Vitis viniferaL.) from São Francisco Valley, Brazil

Abstract: The aim of this study was to investigate the phenolic composition and antioxidant activity of commercial red wines produced from Vitis vinifera L. grapes grown in the São Francisco Valley (SFV), which is a tropical region in northeastern Brazil. All wines showed phenolic compound contents consistent with those of other traditional wine producing regions and high antioxidant activity. In total, 20 phenolic compounds were quantified by RP‐HPLC‐DAD‐FD and the antioxidant activity was positively correlated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
25
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
9
25
2
2
Order By: Relevance
“…The maximum level observed for trans ‐resveratrol was reached with 10 days of maceration (2.2 mg/L). These amounts found in wine are in agreement with the study of Padilha et al () on Syrah wine from the São Francisco Valley (0.77 mg/L). In other regions of the world as Portugal and Italy the amounts of trans ‐resveratrol in Syrah wines ranged from 2.5 and 0.72–5.36 mg/L, respectively (Preti, Vieri, & Vinci, ; Sun, Ribes, Leandro, Belchior, & Spranger, ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The maximum level observed for trans ‐resveratrol was reached with 10 days of maceration (2.2 mg/L). These amounts found in wine are in agreement with the study of Padilha et al () on Syrah wine from the São Francisco Valley (0.77 mg/L). In other regions of the world as Portugal and Italy the amounts of trans ‐resveratrol in Syrah wines ranged from 2.5 and 0.72–5.36 mg/L, respectively (Preti, Vieri, & Vinci, ; Sun, Ribes, Leandro, Belchior, & Spranger, ).…”
Section: Resultssupporting
confidence: 93%
“…The prolonged maceration time (30 days) maintained the amounts of monomeric anthocyanins observed in the Syrah wine produced in the present work. Padilha, Camarão Telles Biasoto, Corrêa, dos Santos Lima, and Pereira () observed in commercial Syrah wine a total monomeric concentration of anthocyanins (36.2 ± 1.6 mg cyanidin 3‐O‐glucoside per liter) in agreement wines of various regions worldwide.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Process of grapes such as dehydration, maceration, and pre‐fermentation could significantly affect the phenolic compound profiles of wines (Alencar et al., ; Panceri & Bordignon‐Luiz, ; Wu et al., ). However, some grape varieties, and therefore the wines, may be genetically richer in polyphenols than the others (Padilha, Camarão Telles Biasoto, Corrêa, dos Santos Lima, & Pereira, ; Poudel, Tamura, Kataoka, & Mochioka, ). The concentration and composition of polyphenols in grapes may show significant differences depending on the variety of grapevine (Montealegre, Peces, Vozmediano, Gascuena, & Romero, ; Ruberto et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These values are considered high since a pH between 3.3 and 3.6 is desirable for red wines, according to the studies performed by Peynaud (1997), in temperate climates. In tropical regions, the pH of wines is higher, as shown by Padilha et al (2017), who suggested that this is due to the higher uptake of minerals by the increased supply of water. In general, the wines with pH values equal to or higher than 3.9 are more susceptible to oxidation, presenting loss of fresh aromas, change in color and least shelf life (RIBÉREAU-GAYON et al, 2003).…”
Section: Wine Physicochemical Propertiesmentioning
confidence: 97%